Management Control System and Financial Performance of Micro Finance Institutions in Central Region Uganda - Arthur, Sunday; Caleb, Tamwesigire; Caroline Masiko, Murezi; George Stanley, Kinyata; Godfrey, Barigye; Keneth, Nuwagira; Moses, Agaba (International Journal of Research, 2019)
Microfinance institutions (MFIs) worldwide have been seen and identified as a vital institution to nations’ quest for solutions to the development challenge (CGAP, 2016). Micro finance in Uganda is a vibrant growing industry and the government of Uganda has over the past decade initiated implemented and or supported various micro credit schemes aimed at fighting poverty in the country. Microfinance has evolved by providing micro credits to respond to the furthermost financial and non-financial needs of the citizens, to eradicate poverty and increase financial inclusion. Most studies undertaken in the past few years have focused mainly on outreach of MFI’s and their impact on profitability and not on internal control system and lack of clarity on the extent to which internal control system influences financial performance (Narver, 2007) will therefore continue to inhibit common understanding and explanation which might deter performance improvement in Ugandan microfinance institutions. Failure by MFIs to monitor portfolio quality closely and take action when necessary and this has threatened the going concern of microfinance industry in Uganda. The study analyzed the relationship between Management control system and financial performance of MFIs in central region Uganda and it was hypothesized that Management control system positively influences financial performance of MFIs in central region Uganda. MFIs have come under spotlight for cases of poor financial performance. Lack of empirical studies to assess the impact of Management control system on the financial performance of microfinance institutions in Uganda is the motivation behind this study. Therefore, this study is important not only because it fills the gap, but also it is set out to address this evident knowledge gap. The study adopted positive-phenomenological, epistemology and quantitative-qualitative methodology dimension with cross sectional and correlation designs, the unit of analysis was Microfinance Institutions registered with Association of Microfinance Institutions, and employees were the units of inquiry. Structural Equations Modeling with Analysis of Moment Structures were used to for statistical modeling Besides, Hierarchical regression was used to test the predictive power of the variables and indicate precisely what happens to the model as different predictor variables are introduced in the model fit. This study revealed that two of the predictor variables are strong predictors of financial performance of MFIs. The study further revealed that Management control system was found to be strongly and positively correlated with financial performance. And Management control system elements were found to be positive predictors of financial performance. The present study supported a multi-theoretic approach in explaining financial performance of MFIs in Uganda. The study supports the stewardship theory in explaining the controls system together with stakeholder as the theories that help in explaining financial performance of MFIs. The study confirmed efficient control system factor structure of observed variables and the latent variables. As a result, the study provided models for efficient Management control systems. These models can then be used to provide a trajectory for improving financial performance of MFIs in Uganda .Regardless of the existence of controls in MFI, the results revealed that Management control systems were less efficient due to lack of close monitoring. It recommended that MFIs should enhance controls to ensure that resources are obtained and used effectively and efficiently in the accomplishment of the organization’s goals .Policy makers, AMFIU, PSFU and MFIs may use these findings as a way of improving financial performance of MFIs in Uganda since the MFIs are great contributors to the Ugandan economy